Inhibition of Xanthine Oxidase Activity by Ethanolic Extract of Piperomia pellucida L., Acacypha indica L. and Momordica charantia L. - Parawansah Parawansah; Nuralifah Nuralifah; Gemini Alam; Rosdiana Natzir (The Indonesian Biomedical Journal, 2016)
BACKGROUND: Uric acid is a final result of purine catabolism, the enzymatic reactions in the body cells from amino acids or ribonucleotide dinucleotide. Peperomia pellucida L. (P. pellucida), Acalypha indica L. (A. indica) and Momordica charantia L. (M. charantia) are plants which have efficacy to reduce levels of uric acid excess. The aim of this research is to find out the effect of ethanol extract of P. pellucida, A. indica and M. charantia in preventing the formation of uric acid excess by inhibiting the action of the enzyme xanthine oxidase and comparing the inhibition activity of xanthine oxidase on treatments.METHODS: The study design is experimental and conducted using the enzyme xanthine oxidase, xanthine (substrate), pH 7.5 phosphate buffer, samples (P. pellucida, A. indica and M. charantia ethanol extracts) and HCL as reaction breaker. Inhibition of xanthine oxidase was determined enzymatically and unreacted xanthine was measured by UV spectrophotometer at 290 nm. The data were expressed as percent inhibition and the inhibitory concentration (IC)50 were determined using linear regresion of inhibition activity vs. concentration.RESULTS: The IC50 of P. pellucida, A. indica and M. charantia ethanol extracts in inhibiting xanthine oxidase were 19.5 ppm, 77.6 ppm and 17.8 ppm, respectively. IC50 of allopurinol was 1.99 μg/ml, and negative control (combination of enzyme and substrate) has absorbance value of 0.75026.CONCLUSION: Ethanol extract of M. charantia showed the most potent inhibition toward xanthine oxidase compared to the other two extracts.KEYWORDS: xanthine oxidase, Peperomia pellucida L., Acalypha indica L., Momordica charantia L.